Effect of sequential subcultures on in vitro proliferation capacity and shoot formations pattern of pineapple (Ananas comosus L. Merr.) over different incubation periods - Hamad, A.M.; Taha, R.M. (2008)
In vitro obtained shoots of pineapple (Ananas comosus L. Merr.) cv Smooth cayenne was cultured on MS medium enriched with 6-benzylaminopurine (BAP) at 3.25 mg l(-1) (14.43 mu M) and indole acetic acid (IAA) at 1.75 mg l(-1) (9.40 mu M) and subcultured for four times at four different incubation periods (30,45, 60 and 75 days). By the fourth subculture, irrespective of incubations periods, the explants lost 50 of its shoot formation capacity. Longer incubation resulted on higher rate and total shoots than a shorter incubation, however, the magnitude of that different varied over subcultures. The difference in shoots formation between the explants incubated for 30 and 75 days was 6 shoots at first, increased to 21 at the third and declined to 11 shoots at the fourth subculture. Over a period of 75 days, the majority of shoots formation occurred during the first 30 days (35) at a rate of 1.5 shoot per week and the last 15 days (40) at a rate of 3.8 shoot per week. In the period between 30 and 60 days, 15 of shoots at rate of 1.8 and 10 at rate of 1.0 shoot per week formed during the first and the second 15 days interval, respectively. Over four consecutive subcultures, explants incubated for 30 days produced the lowest total (1028 shoots) and that incubated for 75 days produced the highest total (120,917 shoots) from a single explant. No significant differences in total were observed between explants incubated for 45 and 60 days over the first three subcultures. However, by the fourth subculture the total of 60 days (14,288 shoots) was two times higher (7163 shoots) than that of 45 days long incubation. (C) 2008 Elsevier B.V. All rights reserved.